The Beneficial Effects of Lactobacillus Strains on Gut Microbiome in Alzheimer’s Disease: A Systematic Review. - Tayebi, M.; Quansah, M.; et al (Healthcare, 2025)
Abstract: Background/Objectives: Growing evidence suggests that the gut–brain axis influences brain function, particularly the role of intestinal microbiota in modulating cognitive processes. Probiotics may alter brain function and behavior by modulating gut microbiota, with implications for neurodegenerative diseases like Alzheimer’s disease (AD). The purpose of this review is to systematically review the current literature exploring the effects of probiotic supplementation on gut microbiota and cognitive function in AD and mild cognitive impairment (MCI). Methods: A comprehensive literature search was conducted across PubMed/Medline, Embase, and Scopus to identify relevant randomized controlled trials (RCTs) from inception to 20 August 2024. The search focused on comparing outcomes between intervention and control/placebo groups. Data searches, article selection, data extraction, and risk of bias assessment were performed in accordance with Cochrane guidelines. Systematic Review Registration: PROSPERO registration no: CRD42023446796. Results: Data from four RCTs involving 293 Individuals (AD and MCI patients) receiving mainly Lactobacillus and Bifidobacterium strains showed some beneficial effects on cognitive function, altered gut microbiota composition, and positively affected metabolic biomarkers. However, variability in microbiota assessment across studies limits the interpretation of results. The limited number and quality of the existing studies make it difficult to draw definitive conclusions from the data. Additional high-quality research is clearly needed. Conclusions: Probiotics show promise as an adjunctive intervention for cognitive decline, but larger, long-term trials are needed to confirm their efficacy and clinical applicability in neurodegenerative diseases like AD.
Research Article
Keywords: Probiotics; Alzheimer’s Disease; Mild Cognitive Impairment; Gut Microbiota